Missing Links Between Gene Function and Physiology in Genomics - Collado-Vides, Julio; Gaudet, Pascale; de Lorenzo, Víctor (Frontiers in Physiology, 2022)
Knowledge of biological organisms at the molecular level is gathered and organized into databases, often organized in ontological frameworks. To enable computational comparisons of annotations across different genomes and organisms, controlled vocabularies have been essential, as is the case in the functional annotation classifications, such as MultiFun and the more widely used Gene Ontology. The function of individual gene products as well as the processes in which collections of them participate constitute a wealth of classes that describe the biological role of gene products in a large number of organisms in the three kingdoms of life. In this contribution we highlight from a qualitative perspective some limitations of these frameworks and discuss challenges that need to be addressed to bridge the gap between annotation as currently captured by ontologies and databases, and our understanding of the basic principles in the organization and functioning of organisms, as illustrated with some examples in bacteria. We hope that raising awareness of these issues will encourage users of Gene Ontology and similar ontologies to be careful about data interpretation and lead to improved data representation.